Antibiotic resistance marker genes as environmental pollutants in GMO-pristine agricultural soils in Austria. (November 2015) - Woegerbauer, Markus; Zeinzinger, Josef; Gottsberger, Richard Alexander; Pascher, Kathrin; Hufnagl, Peter; Indra, Alexander; Fuchs, Reinhard; Hofrichter, Johannes; Kopacka, Ian; Korschineck, Irina; Schleicher, Corina; Schwarz, Michael; et al.
Abstract: Antibiotic resistance genes may be considered as environmental pollutants if anthropogenic emission and manipulations increase their prevalence above usually occurring background levels. The prevalence of aph ( 3′ )- IIa / npt II and aph(3′)-IIIa/npt III – frequent marker genes in plant biotechnology conferring resistance to certain aminoglycosides – was determined in Austrian soils from 100 maize and potato fields not yet exposed to but eligible for GMO crop cultivation. Total soil DNA extracts were analysed by npt II /npt III-specific TaqMan real time PCR. Of all fields 6% were positive for npt II (median: 150 copies/g soil; range: 31–856) and 85% for npt III (1190 copies/g soil; 13–61600). The copy-number deduced prevalence of npt III carriers was 14-fold higher compared to npt II. Of the cultivable kanamycin-resistant soil bacteria 1.8% (95% confidence interval: 0–3.3%) were positive for npt III, none for npt II (0–0.8%). The npt II-load of the studied soils was low rendering npt II a typical candidate as environmental pollutant upon anthropogenic release into these ecosystems. Highlights: ARM genes may act as environmental pollutants under certain conditions. Vital criteria for rating are low endemic presence and anthropogenic ARG immission. Agricultural soils were rarely positive for npt II with few gene copy numbers. Most fields were npt III positive with variable but also increased allele frequency. Npt II/III qualify as pollutants in the tested settings with low endemic abundances. Abstract : ARM genes may be considered as environmental pollutants if anthropogenic activities raise their abundance above naturally occurring background levels in exposed ecosystems.